Strengthening real-time support in wireless networks - Gleeson, Mark (Trinity College (Dublin, Ireland). School of Computer Science & Statistics, 2010)
Wireless networks exhibit unpredictable and varying connection reliability as a result of node mobility and resultant changes in wireless signal propagation. Wireless signal propagation not only depends on the receiver’s mobility but also on unrelated objects both mobile and fixed in the environment. In such dynamic and unknown environments, the provision of real-time communication represents a significant challenge. Not only must transmissions be managed to avoid collisions but may also need to be rescheduled in response to communication failures to ensure success retransmission of frames following failures. Previous work in this area has considered the support for real-time communication with significant constraints, by either relying on master/slave network architectures or through approri knowledge of the network structure. These approaches focus on the creation of collision-free transmission schedules determined off-line, distributed before the execution of the system or through a centralised contention-based resource allocation approach. In this thesis, the need to provide real-time support in a wireless environment in the absence of a master node is discussed. In light of varying communication and node reliability, a distributed solution is chosen to provide resilience in the presence of failures. Unlike other TDMA protocols, the impact of communication-related failures in the form of burst-and single-bit errors is addressed. The protocol reacts to overcome burst errors where possible by exploiting the statistical independence of communication bevi tween individual wireless nodes in conjunction with dynamic rescheduling in response to communication errors to enhance real-time support in the wireless domain. Transmission reliability is addressed through an admissions control process based on clustering transmission resources of destinations with similar transmission probabilities through the application of binomial distribution. This process estimates the overall number of transmissions required to meet the real-time requirements of frames. The application of the clustering algorithm reduces the total number of transmissions required. This thesis makes two key contributions: Firstly, a medium access control protocol, Hierarchical Distributed Time Division Multiple Access (HD-TDMA), is proposed, which incorporates in its design flexibility to permit multiple transmissions per TDMA slot. Secondly, a local, autonomous decision making process exploits the flexibility of HDTDMA to schedule packets to meet real-time requirements while incorporating the ability to dynamically reschedule packets to overcome burst error conditions while, attempting to maintain real-time deadlines.
Keywords: Computer Science, Ph.D.; Ph.D. Trinity College Dublin